The Influence of Compensation, Work Motivation, and Workload on Employee Performance Hr And General Department of PT. Madu Baru - Wahyuningsih, Dewi Sri; Widarta, Widarta; Subarjo, Subarjo (Indonesian Journal Publisher, 2024)
This study aims to determine and test the influence of Compensation (X1), Work Motivation (X2), and Workload (X3) on Employee Performance (Y), with the object of research being employees in the Department of Human Resources and General Affairs of PT Madu Baru. The research design used is quantitative with sampling techniques using non-probability sampling methods with saturated sampling techniques. Data collection was carried out through a questionnaire distributed offline to 77 respondents. Validity was tested using factor analysis, reliability was tested using Alpha Cronbach calculations, and data normality was tested using the Kolmogorov-Smirnov test. The data analysis technique uses multiple linear regression using SPSS software. The results showed that compensation had a negative effect on employee performance, work motivation had a positive effect on employee performance, workload had a positive effect on employee performance, and overall compensation, work motivation, and workload had a simultaneous effect on employee performance.